Design and development of child monitoring track bag using arduino - Arifiyanto Hadinegoro; Faris Fathahillah Herman; Subektiningsih Subektiningsih; Nazaruddin Ahmad (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2024)
This research aims to design and develop a smart bag system for monitoring children using GPS modules, SIM800L modules, and Arduino as hardware components. The main benefit of this system is its capacity to be immediately and instantly monitored through the website, enabling parents to oversee their children effectively. The study employed an experimental method that utilized a literature approach to build the hardware features and websites of a GPS tracker-based track bag monitoring container. After conducting 10 functioning tests, the gadget performed effectively. Tests are conducted both indoors and outdoors, and the findings can accurately determine the position and display the coordinates. The tool demonstrates good accuracy at a range of 8 meters during indoor testing, while outside testing reveals its maximum accuracy at a distance of 21 meters. The utilization of trackers is effectively accomplished through bags, however, this approach may not be appropriate for those with specific requirements and the elderly.